Compensatory Neural Tract from Contralesional Fornical Body to Ipsilesional Medial Temporal Lobe in a Patient with Mild Traumatic Brain Injury: A Case Report. (February 2016) - Jang, Sung Ho; Lee, Han Do
Abstract : ABSTRACT: The authors attempted to demonstrate the compensatory process for an injured fornical crus after mild traumatic brain injury, using follow-up diffusion tensor tractography. A 50-yr-old female patient had a mild traumatic brain injury resulting from a collision that occurred while driving a sedan that was hit from the side. The patient complained of memory impairment since the onset of head trauma and underwent neuropsychologic evaluation at 2 mos after onset with global memory: 77 (6%ile) on the Memory Assessment Scale. She underwent rehabilitation, including cognitive therapy and cholinergic drugs until 12 mos after onset. At that time, she showed improvement of memory impairment with global memory: 90 (25%ile) on the Memory Assessment Scale. On 2-mo diffusion tensor tractography, a discontinuation was observed in the left fornical crus. By contrast, on 12-mo diffusion tensor tractography, the left discontinued fornical crus was shortened; instead, a neural tract from the right fornical body extended to the left medial temporal lobe via the splenium of the corpus callosum and the left fornical column was elongated to the left medial temporal lobe. The authors report on a patient who showed a compensatory neural tract from the contralesional fornical body to the ipsilesional medial temporal lobe via the corpus callosum after mild traumatic brain injury. Abstract : Supplemental digital content is available in the text.